Influence of Mobile-Based Correspondence Information Systems on Administrative Services using SCRUM - Gede, I Komang; Hutnaleontina, Putu Nuniek; Indrawan, I Putu Yoga (Jurnal Ilmiah Manajemen & Bisnis, 2024)
This study aims to design, implement, and analyze the impact of a correspondence information system on administrative services in Antiga Village, with a focus on enhancing transparency and service efficiency. A web- and mobile-based management information system was developed to support this objective. The study was structured using the SCRUM model. In Sprint 1, initial data collection was conducted through interviews and questionnaires distributed to village residents, with a carefully selected population and sample. Sprint 2 involved secondary data analysis from literature and previous studies, providing insights into best practices for village administrative management. Sprint 3 included system design using user interface mockups and process flow diagrams. Sprint 4 concentrated on system implementation and functional testing to validate its capabilities. The results indicate that this system has improved administrative service performance, with functional testing achieving a success rate of 71.43%. Impact analysis shows a positive correlation between system implementation and service improvement, with a determination coefficient of 10.3%, suggesting that additional factors also contribute to service enhancement. This study’s contribution lies in its dual focus on system implementation and comprehensive impact analysis, making it a model for similar administrative contexts. The integration of Panca Satya values provides a framework that strengthens transparency, commitment, and dedication to village development. Intensive technology training was found necessary to enhance technical literacy among village officials, ensuring optimal system operation and broadening benefits such as reduced service times and increased resident satisfaction. This study offers a model for integrated service improvement and underscores the role of technology-driven transparency in advancing rural administrative management, serving as a valuable reference for similar initiatives.